2009
DOI: 10.3329/uhj.v4i2.2074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperuricemia on perinatal outcome in hypertensive disorder of pregnancy

Abstract: The purpose of this study was to detect elevated uric acid level in maternal blood, presumably due to decrease renal urate excretion, for early detection of hypertensive disorder in pregnancy. This study showed that serum uric acid was significantly elevated in all cases of preeclampsia. The present study showed that serum uric acid levels were significantly elevated in eclampsia as compared with the levels in pregnancies complicated by hypertension (p<0.05). The level of uric acid above 4.5 mg/dl is indicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…In high group it is (37.5%) compare to (12.5%) of the low group and (7.1%) of the middle group with p value (0.004). These results are comparable to those of AU Hosna et al 21 , who classified according to uric acid into 3 groups (group A>5mg/dL, group B5-6.9 and group C>7mg/dL) to see the effect on fetal outcome. In (group A) (63.1%) fetus were found with good out come and (23.7%) with bad outcome, (group B) (27.7%) with good outcome and (32.2%) with bad outcome (group C) (9.2%) with good outcome and (44.1%) with bad outcome.…”
Section: Discussionsupporting
confidence: 89%
“…In high group it is (37.5%) compare to (12.5%) of the low group and (7.1%) of the middle group with p value (0.004). These results are comparable to those of AU Hosna et al 21 , who classified according to uric acid into 3 groups (group A>5mg/dL, group B5-6.9 and group C>7mg/dL) to see the effect on fetal outcome. In (group A) (63.1%) fetus were found with good out come and (23.7%) with bad outcome, (group B) (27.7%) with good outcome and (32.2%) with bad outcome (group C) (9.2%) with good outcome and (44.1%) with bad outcome.…”
Section: Discussionsupporting
confidence: 89%
“…Our study concluded that severe preeclampsia cause adverse outcome to neonatal like low birth weight and low Apgar score at 1st and 5th minutes with significant relation, we found same results in Asma Ul Hosna (2008) and James M. Roberts (2005) who reported patients with severe preeclampsia associated with higher incidence of neonatal adverse outcome [31,7]. In this study, neonatal care unit (NCU) admission in hyperuricemia neonates were lower than normal uric acid neonates with significant relation, we found the same result in Singh (2014) study [29] and opposite result with Acien (1990) show that hyperuricemia neonates more admitted to hospital but both studies were non-significant [32].…”
Section: Resultssupporting
confidence: 84%
“…Asma Ul Hosna et al showed that mean serum uric acid is higher in hypertensives than controls 11 . In our study the mean uric acid was 6.08, higher than the mean value of 3.61±0.75 mg/dl in late pregnancy 12 .…”
Section: Discussionmentioning
confidence: 97%